A Novel Bioengineered MicroRNA-127 Prodrug Suppresses The Growth And Metastatic Potential Of Triple Negative Breast Cancer Cells - Umeh-Garcia, Maxine (Cancer Res, 2019)
miR-127 is downregulated in breast cancer, where it has been shown to suppress the proliferation, migration and invasion of breast cancer cells. In triple-negative breast cancer (TNBC), miR-127 downregulation correlates with decreased disease-free and overall patient survival. Tumor suppressor microRNAs may hold therapeutic promise but progress has been limited by several factors, including the lability and high cost of microRNA mimics. Here, we take a novel approach to produce a miR-127 pro-drug (miR-127PD), which we demonstrate is processed to mature, functional microRNA-127-3p in TNBC tumor cells. miR-127PD decreased the viability and motility of TNBC cells, sensitized TNBC cells to chemotherapy, and restricted the TNBC stem cell population. Furthermore, systemic delivery of miR-127PD suppressed tumor growth of MDA-MB-231 and MDA-MB-468 TNBC cells and spontaneous metastasis of MDA-MB-231 cells. In addition, CERK, NANOS1, FOXO6, SOX11, SOX12, FASN, and SUSD2 were identified as novel, functionally important targets of miR-127. In conclusion, our study demonstrates that miR-127 functions as a tumor and metastasis suppressor in triple-negative breast cancer and that delivery of miR-127 may hold promise as a novel therapy.